Outcome of Surgical Management of Ipsilateral Femur and Tibia Fracture: The Floating Knee Injury (Journal of College of Medical Sciences-Nepal, 2023)
IntroductionFloating knee injuries are one of the rare injuries of the lower limb involving fracture of ipsilateral femur and tibia. These injuries are often associated with other systemic injuries and have higher incidence of morbidity and mortality. Often times these fractures can pose difficulty in achieving union and might have residual stiffness around the knee. This study was carried out to assess the functional and radiological outcome of surgical management of floating knee injuries and the associated complications.MethodsA hospital based prospective study including 34 cases of surgically managed floating knee injuries over a period between January, 2017 and December, 2019 with the mean follow-up duration of 15 months was performed. The final outcome was evaluated on the basis of Karlstorm and Orelud criteria.ResultsFinal analysis was done based on the Karlstorm and Orelud criteria after the bony union was achieved. Based on the Karlstorm and Orelud criteria, 44.11% cases had excellent outcome, 29.41% cases had good outcome, 14.7% cases had a fair outcome and 11.76% cases had a poor outcome.ConclusionsFloating knee injuries are severe injuries often associated with polytrauma. Operative management in these complex injuries can yield favorable functional outcome with fewer complications.